Minyak Zaitun dapat Menurunkan Pruritus pada Pasien Diabetes Melitus - Isnaini; Agus Purnama; Rindu (Open Access Jakarta Journal of Health Sciences, 2021)
Introduction: Diabetes mellitus is a metabolic disease of the body due to an absolute or relative disruption of insulin production. The incidence of diabetes is increasing every year. The disorder that is often experienced by sufferers is itching (pruritus). One of the efforts to reduce pruritus is non-pharmacological with olive oil because it can keep the skin moist. Objective: To determine the effect of olive oil on reducing pruritus in diabetes mellitus patients. Methods: Quasy experimental research design with One group pre-test-post test design. Population and sample of 20 respondents, with total sampling technique. Data were collected using a checklist sheet and analyzed the Wilcoxon test. Results: Before giving olive oil, most of the moderate categories were 12 people (60.0%) and after giving olive oil, most of the light categories were 15 people (75.0%). The results of statistical tests obtained ρ = 0.000. Because ρ <0.05 Conclusion: There is an effect of olive oil on reducing pruritus in diabetic patients.